A software tool-box for analysis of regulatory RNA elements - Bengert, Peter (Oxford University Press, 2003)
We describe an integrated tool-box to identify regulatory RNA elements. The RNA analyzer collects general and specific information on any submitted RNA sequence or batch of sequences in FASTA format. It determines and rapidly scans the different regions of an RNA (including 5′ UTR, CDS, 3′ UTR in mRNA) and screens for specific RNA signals (in each of these regions, e.g. polyA-site, AU rich region etc. in 3′ UTR). It runs a fast folding RNA routine to provide an overview of the RNA fold. Furthermore it analyzes structure content, fold energy and stem loops. In addition, consensus templates are used to determine whether there are any functional structures present for translational control (template: IRE), structured RNA (template: tRNA consensus) or catalytic RNA (template: trans-splicing RNA), giving indications as to how well the structures found match to these templates. The tool box has been implemented as a WWW server at http://wb2x01.biozentrum.uni-wuerzburg.de/.